Explaining Job Search Behavior in Unemployed Youngsters Beyond Perceived Employability: The Role of Psychological Capital - Fernández-Valera, Maria Magdalena; Meseguer de Pedro, Mariano; De Cuyper, Nele; García-Izquierdo, Mariano; Soler Sanchez, Maria Isabel (Frontiers in Psychology, 2020)
Job search seems to be a daunting task for youngsters in the Spanish labour market, unfortunately so given that it is the best predictor of getting a job even during economic crisis. Accordingly, it is vitally important to find resources that promote youngsters’ job search. The present study examines the effect of psychological capital on job search through perceived employability in a sample of Spanish unemployed youngsters. We analyzed data of 568 Spanish unemployed youngsters aged 16 to 29 years using structural equation modeling. Results showed that unemployed youngsters who possess high levels of psychological capital also perceive more control over job search which is directly connected with their job search intention. Surprisingly, analyses also showed that perceived employability is not an antecedent of job search. Instead, psychological capital seems to be a more beneficial resource for keeping unemployed youngsters engaged in job search in an adverse economic context.